The multi‐feedstock biorefinery – Assessing the compatibility of alternative feedstocks in a 2G wheat straw biorefinery process. Issue 12 (27th September 2018) - Zhang, Heng; Lopez, Pau Cabañeros; Holland, Claire; Lunde, Alan; Ambye‐Jensen, Morten; Felby, Claus; Thomsen, Sune Tjalfe
Abstract: For second‐generation (2G) bioethanol refineries, the feedstock supply is one of the important parameters in terms of cost and consistency. Biorefineries are in most cases designed for a specific type of feedstock. For some biorefineries, the use of multiple feedstocks is an option, but how would such feedstocks perform when used in a process designed and optimized for a specific feedstock? There is no "one‐size‐fits‐all" processing package, due to variations in composition and structure of different feedstock types, but due to the size of commercial biorefineries, only minor adjustments of the processing parameters are practically feasible. In this study, 16 alternative feedstocks were characterized and compared to the benchmark feedstock wheat straw under identical processing conditions. The alternative feedstocks studied were as follows: barley straw, rye straw, grass straw, oat straw, Norway spruce sawdust, mixed softwood sawdust, oat wrap, biogas fiber, deep litter, washed deep litter, ryegrass fiber, lucerne fiber, ryegrass chaff, mixed grain chaff, rapeseed press cake, and beer production mash. These biomasses varied in carbohydrate content and accessibility after hydrothermal pretreatment. Applying a hydrothermal pretreatment under identical conditions, the subsequent enzymatic convertibility of these biomasses ranged from 0.5% to complete conversion based on their glucan content. Water retention value was determined and correlated with enzymatic convertibility, which provided a simple method for indirect measurement of biomass recalcitrance. Ethanol potentials were estimated based on carbohydrate release from enzymatic hydrolysis, and yeast toxicity test was performed on liquid fractions from hydrothermal pretreatment. Furthermore, a number of key processing indicators, including market price, logistics and availability, were taken into consideration based on a proposed full‐scale 2G ethanol plant in Denmark. The overall results show that while some feedstocks had inferior performance compared to wheat straw, identical or even superior performance was observed from barley, oat, and ryegrass feedstocks. Abstract : In northern Europe, wheat straw is the most important feedstock, which defines the processing parameters in 2G biorefineries, and the compatibility of other common 2G feedstocks to these parameters is investigated in this study. The alternative feedstocks studied were as follows: barley straw, rye straw, grass straw, oat straw, Norway spruce sawdust, mixed softwood sawdust, oat wrap, biogas fiber, deep litter, washed deep litter, ryegrass fiber, lucerne fiber, ryegrass chaff, mixed grain chaff, rape seed press cake, and beer production mash. These biomasses varied in carbohydrate content, carbohydrate accessibility, enzymatic hydrolysis yield, and ethanol potential, after hydrothermal pretreatment.